The Protevangelium of James: A Priestly Drama of Divine Indwelling. - Johnson, Samuel B. (Vigiliae Christianae, 2023)
In view of persistently unresolved questions over whether the assorted segments of the Protevangelium of James can be read as a unified narrative, this study proposes a new account of the work's complete thematic unity. Taking the Nativity as the Protevangelium 's overarching concern, I suggest that its narrative arises principally from the dramatic relationship between purity and divine indwelling characteristic of the Tabernacle narrative (Ex 25–40, Lev 1–16). As the Protevangelium begins to reach its final form during the second century CE, it becomes ordered around narrating the Christ Child as the locus of divine indwelling, a view which binds together the otherwise discordant opening chapters on Mary's upbringing and closing chapters on Zechariah's martyrdom. The Protevangelium invites its readers to consider how the God of Israel could indwell human conception and birth, while neither abolishing the Priestly law nor permitting his unapproachable Presence to suffer diminishment.